PENGARUH PERTUMBUHAN PENDUDUK, RASIO GINI DAN PERTUMBUHAN EKONOMI TERHADAP PENGANGGURAN DI NUSA TENGGARA TIMUR - Pranata, Allen; Rin, Laurensia (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
This research was conducted in districts / cities in East Nusa Tenggara using data from 2018-2020. The urgency of this research includes: 1) Lack of employment availability in East Nusa Tenggara Province; 2) Slow technological development so that human resources are vulnerable to being shifted by the use of technology. The formulation of this research problem includes: 1) What is the effect of population growth on the unemployment rate in East Nusa Tenggara? 2) What is the effect of the Gini ratio index on the unemployment rate in East Nusa Tenggara? 3) What is the effect of economic growth on the unemployment rate in East Nusa Tenggara? 4) What is the effect of population growth, Gini ratio index and economic growth simultaneously on the unemployment rate in East Nusa Tenggara? The research method uses quantitative methods, the population of this study is East Nusa Tenggara Province with a total of 22 cities/regencies. This research refers to the following data analysis techniques: 1) Descriptive analysis test; 2) Test classical assumptions; 3) Panel data regression; 4) Coefficient of correlation and determination; and 5) Test the hypothesis. The results of the partial analysis of population growth have a negative effect and not on the unemployment rate, the gini ratio index has a positive effect on the unemployment rate, economic growth is not significant on the unemployment rate, in a simmerical way population growth, the gini ratio index and economic growth is significant on the unemployment rate.